Xylitol production by cyberlindnera (Williopsis) saturnus, a tropical mangrove yeast from xylose and corn cob hydrolysate - Kamat, S.; Gaikwad, S.; Kumar, A. Ravi; Gade, Wasudeo N. (Journal of Applied Microbiology, 2013)
AimPotential for xylitol production from xylose and corn cob hydrolysate by a tropical mangrove yeast. Methods and ResultsIn the present study, 21 fungi were isolated from detritus-based mangrove wetlands along the Indian west coast. Of these, one yeast isolate had the ability to grow and assimilate xylose producing significant amounts of xylitol (3863gl(-1)). A maximum yield of 054gg(-1) was obtained after 144h of growth on xylose (150gl(-1)) and corn cob hydrolysate (CCH, containing 65gl(-1) xylose). Using biochemical and molecular methods, the yeast was identified as Cyberlindnera (Williopsis) saturnus. Preliminary characterization of enzymes in the cell-free extract revealed that while xylose reductase (XR) preferred NADPH to NADH as cofactor, xylitol dehydrogenase (XDH) was NAD specific. ConclusionsSignificant amounts of xylitol could be produced on CCH using C.saturnus isolated from tropical mangrove wetlands. The yeast has the potential to assimilate rather than ferment xylose as its XR has a preference for NADPH. Significance and Impact of the StudyMicrobes offer an economically viable and green approach for production of xylitol, an industrially important compound. A mangrove ecosystem with its battery of lignocellulolytic enzymes is an ideal location for isolating fungi capable of producing xylitol from agroindustrial waste such as CCH.
Keywords: corn cob hydrolysate; Cyberlindnera; mangrove; Williopsis; xylitol; Xylose; Yeast